2018
DOI: 10.1002/bit.26545
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of high affinity subclasses and glycoforms from serum‐derived IgG using FcγRs as affinity ligands

Abstract: As antibodies continue to gain predominance in drug discovery and development pipelines, efforts to control and optimize their activity in vivo have matured to incorporate sophisticated abilities to manipulate engagement of specific Fc binding partners. Such efforts to promote diverse functional outcomes include modulating IgG-Fc affinity for FcγRs to alternatively potentiate or reduce effector functions, such as antibody-dependent cellular cytotoxicity and phagocytosis. While a number of natural and engineere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 106 publications
1
19
0
Order By: Relevance
“…However, prior subclass switching work does not support a strong role for hinge modification in ADCC, as similar activity of IgG3 relative to IgG1 is typically observed [56,82]. We have previously observed similar induction of NK-degranulation by VRC01 IgG1 and IgG3 [14]. In contrast, a recent study found that hinge extension improved ADCC for one monoclonal antibody, but that this effect was not generalizable across specificities that recognized different epitopes on the same antigen [83].…”
Section: Impact Of Hinge Composition On Other Antibody Functionsmentioning
confidence: 80%
See 4 more Smart Citations
“…However, prior subclass switching work does not support a strong role for hinge modification in ADCC, as similar activity of IgG3 relative to IgG1 is typically observed [56,82]. We have previously observed similar induction of NK-degranulation by VRC01 IgG1 and IgG3 [14]. In contrast, a recent study found that hinge extension improved ADCC for one monoclonal antibody, but that this effect was not generalizable across specificities that recognized different epitopes on the same antigen [83].…”
Section: Impact Of Hinge Composition On Other Antibody Functionsmentioning
confidence: 80%
“…While other factors such as antigen affinity and antigen density have also been associated with modulating ADCC activation [85], the most widely described means to enhanced ADCC activity is via variable fucosylation of the Fc domain. This effect is apparent in the potentiated ability of afucosylated VRC01 IgG1 to induce NK cell degranulation relative to fucosylated IgG1 or IgG3 types, whereas no activity was observed for aglycosylated IgG1 [14]. Antibody glycosylation status was not determined nor controlled for the majority of antibody variants evaluated in this study.…”
Section: Impact Of Hinge Composition On Other Antibody Functionsmentioning
confidence: 88%
See 3 more Smart Citations